Electromyographyc evaluation of movements of lower limb in double pulley system equipment: Comparison between gastrocnemius (caput laterale) and gluteus maximus - Tassi, Nadir [UNESP]; Valenti, Vitor Engrácia [UNESP] (My University, 2007)
It was evaluated movements of lower limb in the double pulley system equipment on ten male volunteers during contraction of gastrocnemius (caput laterale ) and gluteus maximus muscles in the following movements: 1) hip extension with extended knee and erect trunk, 2) hip extension with flexed knee and erect trunk, 3) hip extension with flexed knee and erect trunk, 3) hip extension with extended knee and inclined trunk, 5) hip abduction along the midline, 7) hip abduction with extension beyond the midline, 8) adduction with hip flexion beyond the midline, 8) adduction with hip flexion beyond the midline, and 9) adduction with hip extension beyond the midline. Myoelectric signals were taken up by Lec Tec surface electrodes connected to a 6-channel Lynx electromyographic signal amplifier coupled with a computer equipped with a model CAD 10/26 analogue digital conversion board and with a specific software for signal recording and analysis. We observed weak gastrocnemius muscle activity for all movements studied. In the case of gluteus maximus, the most important potentials were observed for movement 2, while for the remaining movements the actions were of reasonable intensity. Compared to gluteus, gastrocnemius was less required for all movements.
Keywords: Double pulley; Electromyography; Gastrocnemius; Gluteus Maximus; abduction; adduction; adult; controlled study; electrode; electromyography; gastrocnemius muscle; gluteus maximus muscle; hip; human; human experiment; kinesiology; knee function; limb movement; male; muscle action potential; muscle contraction; myoelectricity; normal human; weight lifting; Adolescent; Adult; Exercise Test; Hip Joint; Humans; Knee Joint; Male; Movement; Muscle Contraction; Muscle, Skeletal; Range of Motion, Articular